Research Trend and Future Perspectives of Traditional Chinese Medicine for Atopic Dermatitis from 2004 to 2023: A Bibliometric Analysis - Feng H; Qin Y; Li Y; Li S; Zheng Y; Yan J; Xu R; Yu S; Liang R; Wang J; Zou H (Dove Medical Press, 2024)
Huishang Feng,1,2 Yeping Qin,3 Yuanwen Li,4 Shuo Li,5 Yuyi Zheng,6 Juntang Yan,6 Rongting Xu,6 Shulin Yu,7 Ru Liang,7 Jiayu Wang,7 Huiqin Zou6,7 1Department of Dermatology, Dongzhimen Hospital Beijing University of Chinese Medicine, Beijing, People's Republic of China; 2Second Clinical Medical School, Beijing University of Chinese Medicine, Beijing, People's Republic of China; 3Department of Dermatology, Chongqing Traditional Chinese Medicine Hospital, Chongqing, People's Republic of China; 4Department of Dermatology, Dongfang Hospital, Beijing University of Chinese Medicine, Beijing, People's Republic of China; 5Department of Basic Products, China Mobile Communications Group Co., Ltd. Government and Enterprise Customer Branch in Beijing, Beijing, People's Republic of China; 6Ministry of Education Science and Technology Inspection Department, Beijing University of Chinese Medicine, Beijing, People's Republic of China; 7School of Chinese Materia Medica, Beijing University of Chinese Medicine, Beijing, People's Republic of ChinaCorrespondence: Yuanwen Li, Department of Dermatology, Dongfang Hospital Beijing University of Chinese Medicine, No. 6 Fangxingyuan Fengtai District, Beijing, 100078, People's Republic of China, Tel/Fax +86-1067689620, Email 15810104902@163.com Huiqin Zou, Ministry of Education Science and Technology Inspection Department, Beijing University of Chinese Medicine, No. 11 Beisanhuan Donglu Chaoyang District, Beijing, 100029, People's Republic of China, Tel +86-1064287526, Fax +86-1064287502, Email huiqin.zou@bucm.edu.cnAim: The application of bibliometric analysis gives insights into research trend and future perspectives. This paper aims to understand the current status of studies on traditional Chinese medicine (TCM) in the treatment of atopic dermatitis (AD), and to investigate the cooperation network, hotspots and trends in the field.Methods: The original data were retrieved from the Web of Science Core Collection by searching for the topic "atopic dermatitis" and "traditional Chinese medicine" with the time span of 2004- 2023. Microsoft Excel was used to create statistical tables and charts, whereas CiteSpace and VOSViewer were applied for knowledge mapping.Results: In total, 252 publications were identified and downloaded. Current research on TCM treating AD is in the steady growth period. China has the largest number of publications, whereas the USA has the greatest international influence. Notably, the Arab Emirates, Malaysia, India and Bangladesh all have a high research impact but with a low amount of publications. Universities in Hong Kong China have the largest number of publications, but their interaction with other institutions is very poor. The top three most productive authors are all from Hong Kong, having a strong collaboration network with each other. The popular research topics in this field are "children" "cell" "activation" "nf kappa b" "inflammation" "asthma" "extract" "management" and "cytokine". According to the analysis of leading co-cited journals and authors, "J ETHNOPHARMACOL" has the largest amount of citations whilst "AM J CHINESE MED" the strongest academic influence. The largest number of co-cited authors comes from "Hon Karn-Lun Ellis", a well-known scholar from Hong Kong.Conclusion: TCM has been widely used in AD treatment, honored for its individualized therapeutic concepts of evidence-based treatment. The academic community must form a continuous and deep-going pattern to achieve higher international influence and a stronger research degree in this field.Keywords: atopic dermatitis, traditional Chinese medicine, bibliometrics, knowledge mapping, visual analysis